2021
DOI: 10.3390/ijms22137150
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis Identifies Sex-Specific Gene Expression Changes in Blood of Amyotrophic Lateral Sclerosis Patients

Abstract: Understanding the molecular mechanisms underlying the pathogenesis of amyotrophic lateral sclerosis (ALS), a devastating neurodegenerative disease, is a major challenge. We used co-expression networks implemented by the SWitch Miner software to identify switch genes associated with drastic transcriptomic changes in the blood of ALS patients. Functional analyses revealed that switch genes were enriched in pathways related to the cell cycle, hepatitis C, and small cell lung cancer. Analysis of switch genes by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…For instance, CRISPR/Cas9 gene-editing of HERV-K reduced the expression of SF2/ASF (splicing factor 2/alternative splicing factor) and TDP-43 mRNA levels in vitro (Ibba et al, 2018 ). Recently, switch genes identified in the blood of ALS were enriched in pathways related to viral infection (Santiago et al, 2021 ). Interestingly, switch genes identified in the female datasets were associated with the Epstein-Barr virus, hepatitis B, and hepatitis C. The link between viral infection and carcinogenesis and ALS warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, CRISPR/Cas9 gene-editing of HERV-K reduced the expression of SF2/ASF (splicing factor 2/alternative splicing factor) and TDP-43 mRNA levels in vitro (Ibba et al, 2018 ). Recently, switch genes identified in the blood of ALS were enriched in pathways related to viral infection (Santiago et al, 2021 ). Interestingly, switch genes identified in the female datasets were associated with the Epstein-Barr virus, hepatitis B, and hepatitis C. The link between viral infection and carcinogenesis and ALS warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that dysregulated expression of astrocyte elevated gene 1 (AEG1) and the inhibition of the PI3K-AKT pathway were associated with cell death in ALS motor neurons (Yin et al, 2015 ). Moreover, PI3K-AKT was the most significantly enriched pathway identified in switch genes obtained from males with ALS (Santiago et al, 2021 ). These studies suggest that targeting the PI3K-AKT pathway may be a possible therapeutic route in ALS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations